Black Soldier Fly (Hermetia illucens) Prepupa Phase Fermentation by Organic Acids to Decrease Chitin Content - Muheri Indra Aja Nasution; Yunilas; E Mirwandhono (Jurnal Peternakan Integratif, 2020)
Black Soldier Fly has high protein but there are anti-nutrients, namely the presence of chitin content that cannot be digested by livestock such as poultry and monogastrics. Chitin is a natural polysaccharide that is abundantly found from crustacean organisms and insects. Chitin is usually bound to the shell or exoskeleton, proteins, minerals and pigments. Black Soldier Fly in the prepupa phase has high protein, dark brown body and a rather hard exoskeleton which causes a high chitin content. The aim of this research was to determine the concentration of propionic and formic acids which could reduce the chitin content of the prepupa phase of the Black Soldier Fly (Hermetia illucens) fermentation. This study used a completely randomized design (CRD) with five treatments, namely P1 = (BSF added 50% propionic acid + 50% formic acid), P2 = (BSF added 80% propionic acid and formic acid + 20% aquadest), P3 = (BSF added 60% propionic and formic acids + 40% aquadest), P4 = (BSF added 40% propionic and formic acids + 60% aquadest), P5 = (BSF added 20% propionic acid and formic acid + 80% aquadest) with three repetitions. The results of this study indicate that the P1 treatment (addition of 50% propionic acid + 50% formic acid) resulted in the lowest reduction in chitin content, namely (11.00%), pH value (4.7), total titrated acid (0.014%) and organoleptic (light brown color, very sour aroma and harsh texture).